County Education Bursary Fund Influence On Access To Secondary Education In Siaya County, Kenya - Oketch, Dickens; Sika, James Ochieng; Gogo, Julius otieno (Advances in Social Sciences Research Journal, 2019)
Globally, there exist bursary schemes that are in place to enhance access and equity in the provision of education to the disadvantaged. In Kenya, there have been bursary schemes that enhances access and equity in the provision of secondary school education.With Siaya County’s 16% of the population having secondary school education, below the neighbouring Kisumu county’s 25%, Vihiga county’s 20% and Kakamega county’s 19%, coupled with inequity in bursary distribution, the County Government of Siaya came up with Siaya County Educational Bursary Fund (SCEBF) to help improve access and equity in the acquisition of secondary school education. The purpose of the study was to examine the extent to which the bursary scheme was equitably distributed in Siaya county. Objectives of the study was establish extent to which county education bursary fund allocation to the recipient influences access to secondary education in Siaya County. Descriptive survey and correlational research designs were used in the study. A third of the principals’ population which is 68 secondary school principals and 425 students sampled using Yamane’s formular formed the study sample. The study results indicates that SCEBF allocation had a unique significant contribution to access to secondary education (ß=.564, p=.000). the findings further show that enrollment changed at about 31.8% due to funding allocation in the county. The study recommended that there is need to increase allocation of bursary fund to enhance access to secondary education in the county.